DEFAMATION UNDER THE LAW NUMBER 11 OF 2008 ON INFORMATION AND ELECTRONIC TRANSACTION - Ramadhan, Anna Rahmania (Jurnal IUS, 2015)
In Indonesiaâs criminal law act, a deed of defamation also called as an insolence or sacrilege toward a person. According to Article 27 Paragraph (3) Law Number 11 of 2008 concerning Electronic information and transaction (EIT), the acts of defamation includes distribution, transmission and production of accessible electronic information. Article 27 Paragraph (3) of EIT law was implemented on defamation case which conducted by Prita Mulyasari where she was pleaded innocence by board of judges. Whereas in another similar case the defendant namely Farah, was already meet the substance of Article 17 Paragraph (3) of EIT law yet sued by Article 310 and 311 of Criminal Law Act by prosecutor in the trial. Therefore, there were indications of law miss-implementation in similar cases.Keywords: Criminal law, Defamation.